Nutrient and pathogen removal from anaerobically treated black water by microalgae - Slompo, Nathalie Dyane Miranda; Quartaroli, Larissa [UNESP]; Fernandes, Tânia Vasconcelos; Silva, Gustavo Henrique Ribeiro da [UNESP]; Daniel, Luiz Antonio (Elsevier, 2020)
The demand for systems that efficiently and sustainably recover value-added compounds and materials from waste streams is a major challenge. The use of wastewater as a source for recovery of carbon and nutrients is an attractive and sustainable alternative. In this study, anaerobically treated black water was treated in photobioreactors (PBRs) inoculated with Chlorella sorokiniana, and the process was investigated in terms of phosphorus and nitrogen removal, biomass growth, and the removal of pathogens. The consumption of bicarbonate (alkalinity) and acetate (volatile fatty acids) as carbon sources by microalgae was investigated. The average nutrient removal achieved was 66% for N and 74% for P. A high consumption of alkalinity (83%) and volatile organic acids (76%) was observed, which suggests that these compounds were used as a source of carbon. The biomass production was 73 mg L−1 day−1, with a mean biomass of 0.7 g L−1 at the end of the batch treatment. At the end of the experiments, a log removal/inactivation of 0.51 log for total coliforms and 2.73 log for Escherichia coli (E. coli) was observed. The configuration used, a flat-panel PBR operated in batch mode without CO2 supplementation, is a cost-effective and environmentally sustainable method for recovering of nutrients and production of algal biomass.
Keywords: Chlorella sorokiniana; Decentralized sanitation; Escherichia coli; Nitrogen; Phosphorus; Wastewater